Falling Bodies on Earth at Constant Acceleration Due to Gravity Exhibit Universal Mass-Energy Equivalence Relation - Chanana, Ravi Kumar (European Journal of Applied Sciences, 2024)
In this research article, it is shown that a falling body on earth at constant acceleration due to gravity will also exhibit the universal mass-energy equivalence relation given as dE/E = dm/m, neglecting a 1 to 2 % change in potential energy due to the change in height.